A study of subtle blood brain barrier disruption in a placebo-controlled trial of natalizumab in relapsing remitting multiple sclerosis - Soon, Derek; Altmann, Daniel R.; Fernando, Kryshani T.M.; Giovannoni, Garin; Barkhof, Frederick; Polman, Chris H.; O’Connor, Paul; Gray, Bruce; Panzara, Michael; Miller, David H. (Journal of neurology, 2007)
Natalizumab, an anti-alpha4 integrin antibody, significantly reduces the number of visibly enhancing multiple sclerosis (MS) lesions. In this substudy of a 2-year trial of natalizumab monotherapy versus placebo, contrast-enhanced imaging investigated for subtle blood brain barrier (BBB) leakage in relapsing remitting (RRMS) patients, and whether such leakage is modified by natalizumab. After 24 weeks on treatment, 40 patients from 3 centres (27 on natalizumab and 13 on placebo) were studied. T1 weighted images were obtained before and at set timepoints up to 46 minutes after gadolinium (Gd)-DTPA (0.3 mmol/kg to 18 patients, 0.15 mmol/kg to 22). Paired regions of interest were placed around non-enhancing lesions and contralateral normal appearing white matter (NAWM). BBB leakage was inferred through post-Gd T1 weighted signal intensity (SI) change. SI change was greater in T2 non-enhancing lesions than paired NAWM at all timepoints (P<0.005), indicating BBB leakage in lesions. No significant difference in inferred BBB leakage was observed between treatment arms as measured by SI change of lesions (P>0.05 for all timepoints, joint test P=0.24), or in SI change of NAWM (joint test P=0.37). T1 hypointense and isointense lesions exhibited similar SI changes (joint test P=0.12). There is evidence of a subtle BBB leakage within visibly non-enhancing lesions in RRMS that was not modified by alpha4 integrin blockade in this substudy cohort.